Continuing Disputes and Validity of Voting for the Regent and Deputy Regent of Yalimo Regency in Papua Indonesia - Adiwijaya; Daniel Yusmic Foekh; Manotar Tampubolon (Britain International for Academic Research (BIAR) Publisher, 2022)
This study examines the disputed decisions made by the Constitutional Court of the Republic of Indonesia on the election of the Regent and Deputy Regent of Yalimo Regency, Papua Province, in 2020 that do not adhere to the principle of permanent and final legal force. The Constitutional Court's decision on the dispute over the election of the elected Regent and Deputy Regent resulted in a lengthy case due to the possibility of re-election, which still resulted in general election disputes. The author discusses the consequences of re-election, which has the potential for ongoing disputes at the Constitutional Court of the Republic of Indonesia, as well as non-compliance with the principle of final punishment, which has permanent legal force from the standpoint of fairness and justice. Findings from the study of the proposed candidate having been sentenced by the court, as well as the validity of the vote count results in the District that has been declared valid and not re-voted in the Constitutional Court Decision Number 97/PHP.BUP-XIX/2021 (Study of Constitutional Court Decision Number 145/PHP BUP-XIX/2021) are also presented. According to this study, in the dispute over the election of Yalimo's regent and deputy regent, the judge decided on the same case, which had permanent legal force and violated the principle of legal certainty.